(Satpol PP) - Hamdan Bahalwan; Ratna Puspitasari; Faza Wahmuda (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2024)
The Civil Service Police Unit or The Municipal Police Force (Satpol PP) is tasked with enforcing regional regulations, maintaining public order, and protecting the public. Officers often face risks in the field, such as regulating markets and land at risk of clashes with sellers and thugs. Safety vests are needed because they can protect vital points from the dangers of beatings or sharp object attacks. Another function can be used to indicate the Satpol PP identity so that it is better known to the public. This study aims to redesign a safety vest that can be used in various field duty conditions. The research method uses a mixed method, namely by combining qualitative and quantitative methods. Data were collected through observation, interviews, and online questionnaires. The resulting data analysis is in the form of a redesign of a multifunctional vest to meet the security needs of Satpol PP. The application of graphic design with the selection of colors and shapes produces characters that match the identity of Satpol PP officers.